Aha over Haha: Brands benefit more from being clever than from being funny. Issue 1 (1st June 2022) - Howe, Holly S.; Zhou, Lingrui; Dias, Rodrigo S.; Fitzsimons, Gavan J.
Abstract: We examine whether the cleverness of a brand's humor attempt affects consumers' brand attitudes and engagement. A clever humor attempt is any humor attempt wherein the consumer feels she must make mental connections to solve the joke (e.g., understand a cultural reference, understand the dual meaning of a pun). Across five studies, we demonstrate that as the cleverness of a humor attempt increases, consumers report higher brand attitudes and are more engaged with the brand. This effect is mediated by perceptions of brand warmth and competence and moderated by consumers' need for cognition.